Influence of Zr addition on the microstructure and mechanical properties of 9CrTi-ODS steels. (December 2021) - Wang, Yingjie; Xu, Shuai; Jia, Haodong; Tong, Zhenfeng; Zhou, Zhangjian
Highlight: The addition of Zr shows positive effects on microstructure and mechanical property. The 9CrTiZr-ODS steel has excellent comprehensive mechanical properties. Zr addition can inhibit the formation of Y-Ti-O particles and form Y-Zr-O particles. The reason for properties improvement was explained by the ODS steel stiffness formula. Abstract: The effects of zirconium (Zr) addition on the microstructure and mechanical properties of a 9CrTi-ODS steel have been investigated. The addition of Zr is beneficial to refine grain size and increase dislocation density. The average size of dispersed oxide particles decreased and the number density increased after adding Zr. The chemical composition of the nanoscale oxide particle changes from Y-Ti-O to Y-Zr-O due to the addition of Zr. The Y-Zr-O particles are mainly trigonal δ-phase Y4 Zr3 O12 oxide. The mechanical properties at 25 °C, 500 °C, 650 °C and 700 °C were measured using uniaxial tensile tests. The ultimate tensile strength (UTS) of Zr added sample reaches about 1000 MPa with the total elongation of 17 % at room temperature, and its ultimate tensile strength exceeds 300 MPa at 700 ℃, which is much higher than that of Zr free sample.